Ultrasensitive Reverse Transcription-PCR Assay for Quantitation of Human Immunodeficiency Virus Type 1 RNA in Plasma - Sun, Rita (American Society for Microbiology, 1998)
With the recent introduction of combination therapy, human immunodeficiency virus type 1 (HIV-1) RNA levels in plasma have been dramatically reduced, frequently to below the limit of quantitation (400 copies/ml of plasma) of the AMPLICOR HIV-1 MONITOR Test (Roche Diagnostic Systems). To achieve enhanced sensitivity of the AMPLICOR HIV-1 MONITOR Test, a modified specimen preparation procedure that allows input of RNA from 10-fold more plasma per amplification reaction was developed. This “ultrasensitive” method allows the accurate quantitation of plasma HIV-1 RNA levels as low as 50 copies/ml. A precision study yielded average within-run and between-run coefficients of variation (CV) of 24.8 and 9.6%, respectively. A multicenter reproducibility study demonstrated that the laboratory-to-laboratory reproducibility of this assay is good, with an average CV of 32%. The linear range of this test is between 50 and 50,000 copies/ml of plasma. RNA concentrations measured by the ultrasensitive and standard HIV-1 MONITOR tests exhibited good agreement within the shared linear range of the two methods. The two measurements were within a factor of 2 for 91% of the specimens tested, with the concentration measured by the ultrasensitive method being only slightly lower (median, 22% lower). Preliminary studies suggest that this assay will prove to be useful for predicting the stability of viral suppression in patients whose RNA levels drop below 400 copies/ml in response to highly active antiretroviral therapy.